Determination of acidity constants, ionic mobilities, and hydrodynamic radii of carborane-based inhibitors of carbonic anhydrases by capillary electrophoresis - Šolínová, Veronika; Brynda, Jiří; Šícha, Václav; Holub, Josef; Grűner, Bohumír; Kašička, Václav (Electrophoresis, 2021)
Capillary electrophoresis (CE) has been applied for determination of the thermodynamic acidity constants (pKa ) of the sulfamidoalkyl and sulfonamidoalkyl groups, the actual and limiting ionic mobilities and hydrodynamic radii of important compounds, eight carborane-based inhibitors of carbonic anhydrases, which are potential new anticancer drugs. Two types of carboranes were investigated, (i) icosahedral cobalt bis(dicarbollide)(1-) ion with sulfamidoalkyl moieties, and (ii) 7,8-nido-dicarbaundecaborate with sulfonamidoalkyl side chains. First, the mixed acidity constants, pKamix , of the sulfamidoalkyl and sulfonamidoalkyl groups of the above carboranes and their actual ionic mobilities were determined by nonlinear regression analysis of the pH dependences of their effective electrophoretic mobility measured by capillary electrophoresis in the pH range 8.00-12.25, at constant ionic strength (25 mM), and constant temperature (25°C). Second, the pKamix were recalculated to the thermodynamic pKa s using the Debye-Hückel theory. The sulfamidoalkyl and sulfonamidoalkyl groups were found to be very weakly acidic with the pKa s in the range 10.78-11.45 depending on the type of carborane cluster and on the position and length of the alkyl chain on the carborane scaffold. These pKa s were in a good agreement with the pKa s (10.67-11.27) obtained by new program AnglerFish (freeware at https://echmet.natur.cuni.cz), which provides thermodynamic pKa s and limiting ionic mobilities directly from the raw CE data. The absolute values of the limiting ionic mobilities of univalent and divalent carborane anions were in the range 18.3-27.8 TU (Tiselius unit, 1 × 10-9 m2 /Vs), and 36.4-45.9 TU, respectively. The Stokes hydrodynamic radii of univalent and divalent carborane anions varied in the range 0.34-0.52 and 0.42-0.52 nm, respectively.
Keywords: karboanhydrasy; Capillary electrophoresis; Stokes hydrodynamic radii; Ions; kyseliny; Acid dissociation constant; Acids; ionty; Hydrodynamics; Electrophoresis, Capillary; elektroforéza kapilární; Hydrogen-Ion Concentration; Carbonic Anhydrases; Limiting ionic mobilities; Carboranes; koncentrace vodíkových iontů; hydrodynamika